Pengaruh Promosi Jabatan dan Persepsi Keadilan Kompensasi Terhadap Kepuasan Kerja Karyawan Pada Toko Hana Elektronik - Putri, Aura; Alam, Iskandar Ali; Sanida, Nuris (Politeknik Negeri Ambon, 2025)
This study aims to examine the effect of job promotion and compensation fairness on employee job satisfaction at Hana Electronics Store. Using the census method, the entire population of 35 employees was sampled. A quantitative approach was applied with data analysis through multiple linear regression using SPSS version 30. The results of the analysis showed that partially, job promotion has a positive and significant effect on employee job satisfaction. In contrast, compensation equity has no significant effect on employee job satisfaction. Simultaneously, job promotion and compensation equity have a significant effect on job satisfaction. This finding indicates that job promotion is the dominant factor in increasing employee job satisfaction, while compensation equity requires more attention to maximize its impact. Keywords: Position Promotion, Compensation Fairness, and Job Satisfaction.